Mechanism of autophagic regulation in carcinogenesis and cancer therapeutics. (March 2015) - Panda, Prashanta Kumar; Mukhopadhyay, Subhadip; Das, Durgesh Nandini; Sinha, Niharika; Naik, Prajna Paramita; Bhutia, Sujit K.
Highlights: Autophagy implicates cell death and tumor suppressor phenomena. Autophagy exhibits cancer protective mechanism. Autophagy-apoptosis crosstalk determine ultimate fate of a tumor undergoing treatment. Autophagy has chemopreventive role in cancer. Abstract: Autophagy in cancer is an intensely debated concept in the field of translational research. The dual nature of autophagy implies that it can potentially modulate the pro-survival and pro-death mechanisms in tumor initiation and progression. There is a prospective molecular relationship between defective autophagy and tumorigenesis that involves the accumulation of damaged mitochondria and protein aggregates, which leads to the production of reactive oxygen species (ROS) and ultimately causes DNA damage that can lead to genomic instability. Moreover, autophagy regulates necrosis and is followed by inflammation, which limits tumor metastasis. On the other hand, autophagy provides a survival advantage to detached, dormant metastatic cells through nutrient fueling by tumor-associated stromal cells. Manipulating autophagy for induction of cell death, inhibition of protective autophagy at tissue-and context-dependent for apoptosis modulation has therapeutic implications. This review presents a comprehensive overview of the present state of knowledge regarding autophagy as a new approach to treat cancer.